2017
DOI: 10.1089/neu.2016.4900
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 Promotes Recruitment of Microglia/Macrophages in Response to Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a devastating condition, often leading to life-long consequences for patients. Even though modern neurointensive care has improved functional and cognitive outcomes, efficient pharmacological therapies are still lacking. Targeting peripherally derived, or resident inflammatory, cells that are rapid responders to brain injury is promising, but complex, given that the contribution of inflammation to exacerbation versus improved recovery varies with time post-injury. The injury-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…We also saw a significant increases in the astrocyte activation marker S100a6 (1.7 fold), the cytokine Il6 (2.4 fold), and Il33 (1.6 fold) ( Fig. S2A), an astrocytic cytokine implicated in astrocyte-microglia signaling (Wicher et al, 2017). Thus, disruption of circadian function via knockdown of Bmal1 in WT astrocytes induces a cell-autonomous reactive phenotype in vitro.…”
Section: Resultsmentioning
confidence: 78%
“…We also saw a significant increases in the astrocyte activation marker S100a6 (1.7 fold), the cytokine Il6 (2.4 fold), and Il33 (1.6 fold) ( Fig. S2A), an astrocytic cytokine implicated in astrocyte-microglia signaling (Wicher et al, 2017). Thus, disruption of circadian function via knockdown of Bmal1 in WT astrocytes induces a cell-autonomous reactive phenotype in vitro.…”
Section: Resultsmentioning
confidence: 78%
“…Bmal1 knockdown (KD) in astrocytes induced a highly consistent (across 14 independent experiments) 36% increase in Gfap mRNA expression (Figure S2A) as well as a 68% increase in GFAP protein (Figures 2C and 2D). We also saw significant increases in the astrocyte activation marker S100a6 (1.7-fold), the cytokine Il6 (2.4-fold), and Il33 (1.6-fold) (Figure S2A), an astrocytic cytokine implicated in astrocyte-microglia signaling (Wicher et al, 2017). Bmal1 KD in primary astrocytes from Per2 -luciferase reporter mice caused a loss of circadian Per2 rhythms (Figure 2E).…”
Section: Resultsmentioning
confidence: 90%
“…Mice lacking IL-33 had impaired recovery after CNS injury, which is associated with reduced myeloid cell infiltrates and decreased induction of M2 genes at the injury site [173]. Wicher et al (2017) used samples from human TBI microdialysate, tissue sections from human TBI, and mouse models of central nervous system injury and found that expression of IL-33 in the brain was elevated from nondetectable levels, reaching a maximum after 72 h in both human samples and mouse models [174]. The authors have shown that astrocytes and oligodendrocytes were the main producers of IL-33 [174].…”
Section: Interleukin-33mentioning
confidence: 99%
“…Wicher et al (2017) used samples from human TBI microdialysate, tissue sections from human TBI, and mouse models of central nervous system injury and found that expression of IL-33 in the brain was elevated from nondetectable levels, reaching a maximum after 72 h in both human samples and mouse models [174]. The authors have shown that astrocytes and oligodendrocytes were the main producers of IL-33 [174]. Post-TBI brains of mice deficient in the IL-33 receptor, ST2, contained fewer microglia/macrophages in the injured region as compared to the wild-type controls and had an altered cytokine/chemokine profile in response to injury [174].…”
Section: Interleukin-33mentioning
confidence: 99%
See 1 more Smart Citation